Hubungan kebersihan diri dengan kejadian skabies di Panti Asuhan Palangka Raya - Aisza, Nor; Toemon, Agnes Immanuella; Teresa, Astrid; Augustina, Indria; Hanasia (Fakultas Kedokteran Universitas Palangka Raya, 2024)
The occurrence of falls among the elderly is a result of the aging process, which can lead to injuries and physical limitations. A history of falls, gender, and nutritional status are estimated to influence the risk of falling. To evaluate the relationship between a history of falls, gender, and nutritional status and the results of the TUGT using a descriptive analytical design with a cross-sectional approach, the study sample consisted of 30 elderly people. Data analysis was performed using SPSS software, applying Fisher’s Exact Test and Spearman correlation tests. There is a relationship between a history of falls and nutritional status and the results of the TUGT in the elderly with p-value = 0,000. However, no significant relationship was found between gender and the results of the TUGT. This study provides evidence that a history of falls and nutritional status influence balance in the elderly.